Sosialisasi dan Edukasi Gerakan Kang Pisman melalui Program Waste To Food - Al-Amin, Muhammad Insan; Subagja, Yogi Firmansyah; Febriani, Shita Auliya; Nurmalasari, Rina; Putra, Ajietya Hermawan; Muchlis, Fadel Muhammad (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2022)
In an effort to deal with the waste problem in the city of Bandung, it is necessary to start from the starting point or source, namely the household and will require active participation from the community. The purpose of the activities held is to provide the community with understanding and ability in managing waste, so that they have social awareness to change behavior in processing waste through the "Kangpisman Movement". The targets of the activities carried out are educational institutions or active communities, which in the end are able to become the pioneers of implementing the Kangpisman Movement. Counseling to the practice of waste management is a method in this activity. The materials used in the counseling are waste problems in the city of Bandung, solving waste management problems, the Kangpisman program, waste management flow, jobdesc mapping in waste management, work scheduling in waste management, parties involved in waste management, and the benefits obtained in waste management. . After that, the educational materials include the practice of processing organic and inorganic waste, making the Wasima processing process, introducing urban farming. The conclusion of the socialization and education activities shows that the Kangpisman program has been part of the solution for handling waste so far, and Educational Institutions have become an important part of being the driving force for the Kangpisman program in order to create a waste-free area.